(untitled) (Siddhajyoti Interdisciplinary Journal, 2023)
Social networking is an Internet-based technology that helps its users to promote and modification of health-related behaviour. College students can use social media for many reasons, such as accessing health information, as a source of health education, and finding and sharing health information. The study aimed to find out the existing social media use situation and to analyze the facilitating and impeding factors of social media use among college students for health promotion and behavior change. This study was based on a cross-sectional research design. A total of 409 Bachelor level college students were included in the study from three colleges of the Banke district colleges by using a multistage sampling method. The data were collected by using a self-administered questionnaire and analyzed them using SPSS version 20. This study found that 29.4 percent of respondents used Facebook for health communication, and 26.7 percent of respondents used Facebook for watching health -related videos, texts and images . Similarly, the majority of the respondents (79.5%) pointed out that knowledge and skills as one of the motivating / influencing factors of social media use. Based on the present study results, college students use social media to understand and share health information.